Adult-onset systemic autoinflammatory disorders: a clinical approach - T. Borges; A. Barbosa; S. Silva (PAGEPress Publications, 2020)
Autoinflammatory disorders (AIDs) are a subgroup of immune-mediated syndromes that result from a primary dysfunction of the innate immune system. AIDs can be either monogenic or polygenic diseases. Unlike organspecific AIDs, systemic AIDs are characterized by fever and/or elevation of acute-phase reactants. This review aims to describe the most common adult-onset systemic AIDs, focusing mostly on polygenic and mixed-pattern diseases which are expected to be more prevalent in adult patients than monogenic AIDs overall. The literature was searched in Medline database. Organ-specific or childhood-onset systemic AIDs were excluded. AIDs were divided in three distinct groups: mixed-pattern, polygenic and adult-onset monogenic AIDs. Most adult-onset AIDs are polygenic but late-onset disease is not rare among monogenic AIDs such as familial Mediterranean fever (FMF). The diagnosis of systemic AIDs in adults is often delayed due to several factors and sometimes it is only established when amyloidosis or other complications are present. Therefore, it probably makes sense to primarily exclude common AIDs in adult patients with fever of unknown origin (and probably different presentations such as polyserositis) since a high prevalence of adult-onset Still's disease or FMF is usually expected. Colchicine, nonsteroidal anti-inflammatory drugs, steroids, immunosuppressive agents, interleukin-1 inhibitors and tumor necrosis factor antagonists constitute common therapeutic options for systemic AIDs.